Proses Kognisi Peserta Didik Berprestasi Belajar Amat Baik Dan Kurang Dalam Pemecahan Masalah Matematis - Catur Supatmono (UNIKA SANTU PAULUS RUTENG, 2019)
This study aims to determine the cognitive processes of students who have very good and lack of mathematics learning achievement. The subjects of this study consisted of two students with the details of one student having very good mathematics learning achievement and one student having less mathematics learning achievement. Data collection techniques are done by observation, tests, and interviews. Data were analyzed using data processing steps in qualitative research. The results showed that in general, the process of cognition of research subjects who had excellent learning achievement and lacked in solving mathematical problems with broad topic triangles took place in the same groove. However, there are differences in the quality of each element in the process of cognition. There is a tendency, research subjects who have excellent learning achievement have better quality at the stage of perception and short-term memory compared to research subjects who have less learning achievement.